Mediating role of consumer trust in local food restaurants on the relationship between social media marketing and consumer purchase intention in Indonesia - Ratni Prima Lita; Meuthia (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
Regarding the effect of the COVID-19 pandemic on consumer behavior, this study investigates the effect of social media marketing on consumer trust and consumer purchase intention in order to buy online food in West Sumatera, Indonesia. This study also examines the impact of consumer trust as mediating variable between social media marketing and consumer purchase intention. 210 participants were involved by distributing online questionnaires. Data were analyzed using Structural Equation Modelling through SmartPLS 3.0. The result of this study shows the significant influence of social media marketing on consumer trust and consumer purchase intention, also consumer trust significantly influences consumer purchase intention. Consumer trust partially mediated the relationship between social media marketing and consumer purchase intention. Finally, this study contributes to encouraging social media marketing usage for local food businesses in Indonesia. The theoretical and practical implications will provide valuable insight for further study in the food industry related to online consumer purchase intention.